Turning Away from the Big Brother: China’s Search for Alternative Sources of Knowledge During the Sino-Soviet Split - Matten, Marc A. (Comparativ, 2019)
In the rst two decades of the People’s Republic of China transnational science circulation played a signicant role in the country’s socialist reconstruction. In this context, modernization was pursued via translation and transfer of Soviet knowledge, most prominently in the form of the journal Knowledge is Power (Zhishi jiushi liliang). Following the style and ideas of its Soviet namesake Znanie – sila it presented the vision of “tomorrow” – the near future – for young workers and students. Starting its publication in 1956, it supported the state’s call for “marching towards science,” a slogan behind which was China’s awareness of its backwardness in science and technology. Earlier research has shown how ideological campaigns in 1950s China tried